Investigating canonical size phenomenon in drawing from memory task in different perceptual conditions among children - Magdalena Szubielska; Marcin Wojtasiński; Monika Pasternak; Katarzyna Pasternak; Paweł Augustynowicz; Delphine Picard (Scientific Reports)
Abstract The canonical size phenomenon refers to the mental representation of real-object size information: the objects larger in the physical world are represented as larger in mental spatial representations. This study tested this phenomenon in a drawing-from-memory task among children aged 5, 7, and 9 years. The participants were asked to draw objects whose actual sizes varied at eight size rank levels. Drawings were made on regular paper sheets or special foils to produce embossed drawings. When drawing from memory, the participants were either sighted or blindfolded (to prevent visual feedback). We predicted that the drawn size of objects would increase with increasing size rank of objects. The findings supported the hypothesis concerning the canonical size effect among all age groups tested. This means that children aged 5 to 9 represent real-world size information about everyday objects and are sensitive to their size subtleties. Moreover, the drawn size increased with increasing size ranks both within sighted and blindfolded perceptual conditions (however, the slope of functions that best explain the relation between size rank and drawn size varied between the perceptual conditions). This finding further supports the recent evidence of the spatial character of the canonical size phenomenon.